Effect of cutting and packaging type on the conservation of fresh-cut ‘Golden’ pineapple fruit [Ananas comosus (L.) Merr.] - Buitrago-Dueñas, Elkin Mauricio; Dussán-Sarria, Saul; Rivera-Ochoa, María Camila; Ordoñez-Santos, Luis Eduardo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Pineapple is a tropical fruit appreciated worldwide for its flavor, texture and color, and is suitable for minimal processing. The objective of this research was to determine the effect of the cut type and type of container for minimally processed pineapple on quality attributes during refrigeration at 5±1°C and 85-90% relative humidity. During the refrigerated storage, the color, texture and sensorial acceptance were monitored for 12 days. The samples were analyzed statistically by means of a factorial design using completely random subsubdivided plots. The evaluated factors included three cut types and three types of packaging, and the evaluated response variables included quality attributes. All measurements were taken in triplicate. Descriptive statistics, ANOVA and means comparison using Duncan test were used. In general, both the cut type and the type of packaging affected the quality attributes of the ‘Golden’ pineapple during storage. The best preservation condition was pineapple cut into quarter slices and vacuum-packed, reaching 12 days of storage.